MUSTI: Multi-scale spatiotemporal tensor imputation for global leaf area index time series reconstruction - Xinpei Yu; Kai Yan; Jiabin Pu; Jinxiu Liu; Jin Wu; Alexander J.Winkler; Qiao Wang (Remote Sensing of Environment, 2026)

Effects of impurities on the rheological behavior of rare earth concentrate slurry and the regulatory role of retarders - Xiaodong Wang; Xiaowei Zhang; Feng Guo; Yanhong Hu; Jinxiu Wu; Wenjun Fan; Likai Zang; Qifu Yuli; Zhao Yu; Ruifeng Ma (Minerals Engineering, 2026)

Gamma-ray irradiation induces dose-dependent mutational signatures in Ganoderma resinaceum revealed by whole-genome resequencing - Jinxiu Li; Siyang Guo; Dandan Zhang; Minghui Zhao; Lu Cao; Yu Li; Shijun Xiao; Xuerong Han (Fungal Biology, 2026)

ANKFY1 suppresses PDCoV replication by degrading viral nsp8 protein via p62-dependent selective autophagy - Yufan Xu; Yangyang Zhang; Huixin Zhu; Xiaomeng Yu; Jinxiu Lou; Mingyu Liu; Gongguan Liu; Juan Bai; Ping Jiang; Zhen Yang; Xianwei Wang (Veterinary Microbiology, 2026)

Effects of gradual warming and marine heatwaves on the growth and metabolism of Phaeocystis globosa - Jing Wang; Xiaoxia Sun; Jinxiu Wang; Yongfang Zhao; Shujin Guo; Shan Zheng; Junhua Liang; Mingliang Zhu; Rencheng Yu (Harmful Algae, 2026)

Spatiotemporal dynamics of Phaeocystis globosa genotypes in a P. globosa bloom in the Beibu Gulf, China revealed differential contributions to bloom development - Yifei Wang; Jinxiu Wang; Rencheng Yu; Nansheng Chen (Harmful Algae, 2026)

Insights into the flavor enhancement mechanism during dried bonito processing: An integrated analysis of flavoromics and untargeted lipidomics - Jing Yu; Jiayi Ren; Xin Zhang; Jinxiu Shi; Zengyan Yu; Xinpeng Cao; Gang Yu; Yong Xue; Changhu Xue (Food Research International, 2026)

Engineering the biosynthesis of natural lipopeptide octapeptins in Paenibacillus elgii 219 to combat multidrug-resistant - Guangxin Yang; Sheng Huang; Xinchan Wang; Xiuliang Ding; Feiyun Yang; Jinxiu Huang; Aihua Deng; Xiangfang Zeng; Shiyan Qiao; Haitao Yu (Chemical Engineering Journal, 2026)

Cryoprotective role of ice structuring protein/short-chain inulin/trehalose in frozen shrimp surimi: Quality maintenance strategies during freeze-thaw cycles - Jing Yu; Huiyan Zhang; Jinxiu Shi; Xinpeng Cao; Yong Xue; Changhu Xue (Food Chemistry, 2025)

Liver-targeting exosomes loaded naringenin ameliorate metabolic dysfunction-associated steatotic liver disease through ubiquitin-proteasome system initiated lipophagy - Zhenglai Hua; Xiaoyu Li; Liuchunyang Yu; JinXiu Qian; Meng Tian; Xiuyun Bai; Jue Yang; Rongjun Deng; Qiqiong Liu; Cheng Lu; Zhiwen Cao; Yuanyan Liu (Chemical Engineering Journal, 2025)

Genetic diversity and distribution patterns of Phaeocystis globosa in the eastern Chinese coastal seas: Significance of a global intraspecific re-examination - Ling Xiang; Chao Liu; Qingchun Zhang; Junlan Huang; Jinxiu Wang; Rencheng Yu (Marine Environmental Research, 2025)

A strategic study of multi-criteria decision-making: Functional properties and application prospects of five plant protein alternatives to animal-based products - Jinxiu Shi; Jing Yu; Lei Wang; Yong Xue; Changhu Xue (Food Chemistry, 2025)

High-moisture texturization of Antarctic krill (Euphausia superba) meat-based hybrid protein: The synergistic effect of wheat gluten and pea protein - Zengyan Yu; Jing Yu; Lei Wang; Jinxiu Shi; Songgang Xia; Yong Xue; Ningyang Li; Changhu Xue (Food Chemistry, 2025)

Investigating the impact of fecal contamination on antibiotic resistance genes in urban environments using host-associated molecular indicators - Yujing Duan; Hui She; Lingna Jing; Lianrui Duan; Jinxiu Zheng; Ying Shao; Yuxin Che; Yu Shi; Chao Guo; Wenhui Zhao; Tao Yang; Lijun Yang (Environmental Pollution, 2025)

Selection of protocols for phytoplankton pigment analysis: a comparative study - Jinxiu Wang; Fanzhou Kong; Zhuang Niu; Rencheng Yu (Journal of Oceanology and Limnology, 2025)

Bioassay-guided isolation of terpenoids from Rubus rosifolius - Yihao Yin; Jiehui Li; Qi Cao; Jinxiu Yu; Baoli Chen; Zhigang She; Xiuping Zhang; Bo Wang (Phytochemistry Letters, 2025)

A Phaeocystis bloom in the northern Beibu Gulf reflects nutrient-driven shifts in dominant phytoplankton taxa - Zhengxi Zhou; Rencheng Yu; Zhenjun Kang; Jinxiu Wang; Chaojiao Sun; Ruth Eriksen; Fanzhou Kong; Qingchun Zhang; Huixia Geng; Yue Zhao; Chunhui Wu (Environmental Pollution, 2025)

Metabolomics-based estimation of activated sludge microbial composition and prediction of filamentous bulking - Jie Wang; Feng Ju; Pingfeng Yu; Jinxiu Lou; Minxi Jiang; Huichun Zhang; Huijie Lu (Water Research, 2024)

A novel flavonoid and other constituents from Rubus rosifolius S.Vidal (Rosaceae) - Yihao Yin; Yunqi Huang; Wencong Yang; Jie Yuan; Minli Xie; Yongfeng Miao; Jinxiu Yu; Juncong Wang; Xiuping Zhang; Bo Wang (Natural Product Research, 2024)

Attitude synchronization control for multiple spacecraft: A preassigned finite-time scheme - Hui-Jie Sun; Yu-Yao Wu; Jinxiu Zhang (Advances in Space Research, 2024)

Multifunctional photothermal PB@EGCG-Sr nanocoating design on titanium surface: To achieve short-term rapid osseointegration and on-demand photothermal long-term osteogenesis - Pengfei Gao; Yangpeng Zuo; Yulu Yang; Jinxiu Yu; Wuzhe Fan; Ruqing Bai; Weihu Yang; Kaiyong Cai (Chemical Engineering Journal, 2023)

Characterizing annual dynamics of urban form at the horizontal and vertical dimensions using long-term Landsat time series data - Yixuan Wang; Xuecao Li; Peiyi Yin; Guojiang Yu; Wenting Cao; Jinxiu Liu; Lin Pei; Tengyun Hu; Yuyu Zhou; Xiaoping Liu; Jianxi Huang; Peng Gong (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Mechanism of β-blocker biodegradation by wastewater microorganisms - Ming Yi; Jinxiu Lou; Wanlu Zhu; Dan Li; Pingfeng Yu; Huijie Lu (Journal of Hazardous Materials, 2023)

Effect of morphology and simultaneous sulfation on Fe doped CeO2 for selective catalytic reduction of NO with NH3 - Jinxiu Wang; Yuqiu Liu; Xianfang Yi; Yanting Chen; Yanke Yu; Jinsheng Chen (Fuel, 2023)

Newly recorded bloom-forming dinoflagellate Gymnodinium impudicum in Haizhou Bay, Yellow Sea, China - Jinxiu Wang; Fanzhou Kong; Yunfeng Wang; Nanjing Ji; Minjie Song; Zhangxi Hu; Zhuang Niu; Chao Liu; Xin Wang; Yuanyuan Sun; Rencheng Yu; Tian Yan (Journal of Oceanology and Limnology, 2022)

Dynamics of Phaeocystis globosa bloom and implications for its seed sources in the Beibu Gulf, China - Zhuang Niu; Weibing Guan; Jinxiu Wang; Yongquan Yuan; Fanzhou Kong; Chao Liu; Qingchun Zhang; Rencheng Yu (Journal of Oceanology and Limnology, 2022)

Development of high-resolution chloroplast markers for intraspecific phylogeographic studies of Phaeocystis globosa - Qingchun Zhang; Zhuang Niu; Jinxiu Wang; Chao Liu; Fanzhou Kong; Xiaokun Hu; Jiayu Zhao; Rencheng Yu (Journal of Oceanology and Limnology, 2021)

Psychological symptoms in Chinese nurses may be associated with predisposition to chronic disease: a cross-sectional study of suboptimal health status - Jinxiu Zhu; Wenjuan Ying; Li Zhang; Gangyi Peng; Weiju Chen; Enoch Odame Anto; Xueqing Wang; Nan Lu; Shanshan Gao; Guihai Wu; Jingyi Yan; Jianfeng Ye; et al. (EPMA Journal, 2020)
Background Suboptimal health status (SHS) is a reversible state between ideal health and illness and it can be effectively reversed by risk prediction, disease prevention, and personalized medicine under the global background of predictive, preventive, and personalized medicine (PPPM) concepts. More and more Chinese nurses have been troubled by psychological symptoms (PS). The correlation between PS and SHS is unclear in nurses. The purpose of current study is to investigate the prevalence of SHS and PS in Chinese nurses and the relationship between SHS and PS along with predisposing factors as well as to discuss the feasibility of improving health status and preventing diseases according to PPPM concepts in Chinese nurses. Methods A cross-sectional study was conducted with the cluster sampling method among 9793 registered nurses in Foshan city, China. SHS was evaluated with the Suboptimal Health Status Questionnaire-25 (SHSQ-25). Meanwhile, the PS of depression and anxiety were evaluated with Self-Rating Depression Scale (SDS) and Self-Rating Anxiety Scale (SAS) self-assessment questionnaires. The relationship between PS and SHS in Chinese nurses was subsequently analyzed. Results Among the 9793 participants, 6107 nurses were included in the final analysis. The prevalence of SHS in the participants was 74.21% (4532/6107) while the symptoms of depression and anxiety were 47.62% (2908/6107) and 24.59% (1502/6107) respectively. The prevalence of SHS in the participants with depression and anxiety was significantly higher than those without the symptoms of depression (83.3% vs 16.7%, P < 0.001) and anxiety (94.2% vs 5.8%, P < 0.0001). The ratio of exercise habit was significantly lower than that of non-exercise habit (68.8% vs 78.4%, P < 0.001) in SHS group. Conclusions There is a high prevalence of SHS and PS in Chinese nurses. PS in Chinese nurses are associated with SHS. Physical exercise is a protective factor for SHS and PS so that the exercise should be strongly recommended as a valuable preventive measure well in the agreement with PPPM philosophy. Along with SDS and SAS, SHSQ-25 should also be highly recommended and applied as a novel predictive/preventive tool for the health measures from the perspectives of PPPM in view of susceptible population and individual screening, the predisposition to chronic disease preventing, personalization of intervention, and the ideal health state restoring.

Leptin promotes endothelial dysfunction in chronic kidney disease by modulating the MTA1-mediated WNT/β-catenin pathway - Bing Liu; Jiao Qiao; Jinxiu Hu; Minghua Fan; Yanfang Zhao; Hong Su; Ziyang Wang; Qun Yu; Qiqi Ma; Yanmei Li; Zhimei Lv; Rong Wang (Molecular and Cellular Biochemistry, 2020)

Relationships between typhoons, climate and crime rates in Taiwan - Chin-Hsien Yu; Jianhong E. Mu; Jinxiu Ding; Bruce A. McCarl (Natural Hazards, 2017)

New Insight into the Effect of Potassium on Commercial SCR Catalyst: Promotion of Thermal Stability - Yanke Yu; Xiaoran Meng; Jinsheng Chen; Jinxiu Wang; Yanting Chen (Water, Air, & Soil Pollution, 2015)

Formation, regeneration, and transformation of protoplasts of Streptomyces diastatochromogenes 1628 - Zheng Ma; Jinxiu Liu; Xiaozhen Lin; Xuping Shentu; Yalin Bian; Xiaoping Yu (Folia Microbiologica, 2014)

Development of Intergeneric Conjugal Gene Transfer System in Streptomyces diastatochromogenes 1628 and Its Application for Improvement of Toyocamycin Production - Zheng Ma; Jinxiu Liu; Andreas Bechthold; Libin Tao; Xuping Shentu; Yalin Bian; Xiaoping Yu (Current Microbiology, 2014)

S-Adenosylmethionine-induced adipogenesis is accompanied by suppression of Wnt/β-catenin and Hedgehog signaling pathways - Yang Liu; Wentao Lv; Boyang Yu; Tingting Ju; Feiyun Yang; Meihua Jiang; Zuohua Liu; Ling Xu; Wenjuan Sun; Jinxiu Huang; Defa Li; Jingdong Yin (Molecular and Cellular Biochemistry, 2013)

Distribution and enrichment of acid-leachable heavy metals in the intertidal sediments from Quanzhou Bay, southeast coast of China - Gongren Hu; Ruilian Yu; Jinxiu Zhao; Liping Chen (Environmental Monitoring and Assessment, 2011)

Genetic diversity and differentiation of Sclerotinia sclerotiorum populations in sunflower - Ziqin Li; Yingchun Wang; Yu Chen; Jinxiu Zhang; W. G. Dilantha Fernando (Phytoparasitica, 2009)